2010
DOI: 10.1016/j.amjcard.2009.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Function and C-Reactive Protein Levels in Acute Myocardial Infarction

Abstract: To examine left ventricular (LV) function in patients after acute myocardial infarction (AMI) and assess its relation with C-reactive protein (CRP) as a measure of the early inflammatory response. We measured CRP levels early after AMI and correlated them with early structural and functional cardiac alterations. Between November 2002 and December 2007, we prospectively enrolled community subjects who experienced an AMI defined by standardized criteria, measured CRP and obtained an echocardiogram. The study con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…In 2000, Ridker et al [22] found elevated hs-CRP to be predictive of cardiovascular disease in women. Elevated hs-CRP has since been associated with poor prognostic indicators, such as decreased LVEF and diastolic dysfunction, in patients with a variety of cardiovascular maladies including acute myocardial infarction [23], chronic stable angina [24], left ventricular systolic heart failure [17], idiopathic left ventricular dysfunction [16], and congestive heart failure [15,25]. The results LVEF left ventricular ejection fraction, HRT/OCP hormone replacement therapy/oral contraceptive pills presented here suggest that elevated serum hs-CRP may also be useful as a biomarker for early detection of risk for cardiotoxicity in breast cancer patients undergoing adjuvant trastuzumab treatment combined with standard chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In 2000, Ridker et al [22] found elevated hs-CRP to be predictive of cardiovascular disease in women. Elevated hs-CRP has since been associated with poor prognostic indicators, such as decreased LVEF and diastolic dysfunction, in patients with a variety of cardiovascular maladies including acute myocardial infarction [23], chronic stable angina [24], left ventricular systolic heart failure [17], idiopathic left ventricular dysfunction [16], and congestive heart failure [15,25]. The results LVEF left ventricular ejection fraction, HRT/OCP hormone replacement therapy/oral contraceptive pills presented here suggest that elevated serum hs-CRP may also be useful as a biomarker for early detection of risk for cardiotoxicity in breast cancer patients undergoing adjuvant trastuzumab treatment combined with standard chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In the scientific literature, conflicting results about the relation of CRP levels and LVEF in patients with ACS have been published. [31][32][33][34] Although it has been reported that CRP adds significant prognostic information to predict heart failure and Inflammation and outcome in acute coronary syndromes Fiechter et al 811 mortality in patients with ACS, 31,32 others found only a relation of inflammation to left ventricular remodeling, irrespective of LV systolic function. 34 The different methodological aspects might explain this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34] Although it has been reported that CRP adds significant prognostic information to predict heart failure and Inflammation and outcome in acute coronary syndromes Fiechter et al 811 mortality in patients with ACS, 31,32 others found only a relation of inflammation to left ventricular remodeling, irrespective of LV systolic function. 34 The different methodological aspects might explain this discrepancy. This includes the use of different CRP assays (high sensitivity CRP versus CRP), disparate time points of blood collection (admission versus CRP maximum), and different tools for assessing LV function (echocardiography vs. angiography).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies [24, 25, 27] in this field assessed LVEF as a continuous variable. Aggelopoulos et al [23] showed that an increase in CRP plasma concentration during 12 h after admission as high as 10 mg/L was an independent predictor of a 6 % augmentation of risk for LVSD at discharge.…”
Section: Discussionmentioning
confidence: 99%